2012
DOI: 10.1002/elps.201200221
|View full text |Cite
|
Sign up to set email alerts
|

IEF‐based multidimensional applications in proteomics: Toward higher resolution

Abstract: This review focuses on the alternative isoelectrofocusing methods and IEF-related techniques in protein analysis and characterization. The main emphasis is placed on the evaluation of the resolving power of new approaches, as well as potential advantages of IEF-related techniques for multidimensional analysis. In particular, the inverse 2D gel electrophoresis where the Mw separation stage precedes IEF mode is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 134 publications
0
11
0
Order By: Relevance
“…Properties of the gradient include the slope and the charge curve near the focusing point. These properties and relationships have been reviewed in detail [6,9]. …”
Section: Introductionmentioning
confidence: 99%
“…Properties of the gradient include the slope and the charge curve near the focusing point. These properties and relationships have been reviewed in detail [6,9]. …”
Section: Introductionmentioning
confidence: 99%
“…Advances in ITP over last two decades have been well monitored and are included in reviews by a number of groups as summarized in Table . This paper presents a detailed review of micro‐ITP (μ‐ITP).…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid advances in proteomics and genomics and the continuously developing field of life sciences, high‐performance separation techniques have become essential for protein research . IEF is a powerful and reliable technique because it preconcentrates proteins, peptides, and other zwitterionic biomolecules, in addition to separating them with high peak capacity .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the implementation of microfluidics in the IEF methodology offers definite advantages over macroscale approaches, including faster separation times, devices with small sample volumes, as well as the potential for automated total analysis formats and increased separation efficiencies . A number of studies have successfully demonstrated IEF in a chip format .…”
Section: Introductionmentioning
confidence: 99%